Natural radionuclides in major aquifer systems of the Parana sedimentary basin, Brazil - Bonotto, Daniel Marcos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
This paper describes the natural radioactivity of groundwater occurring in sedimentary (Bauru and Guarani) and fractured rock (Serra Geral) aquifer systems in the Parana sedimentary basin, South America that is extensively used for drinking purposes, among others. The measurements of gross alpha and gross beta radioactivity as well the activity concentration of the natural dissolved radionuclides (40)K, (238)U, (234)U, (226)Ra, (222)Rn, (210)Pb and (210)Pb were held in 80 tubular wells drilled in 21 municipalities located at São Paulo State and its border with Mato Grosso do Sul State in Brazil. Most of the gross alpha radioactivity data were below 1 mBq/L, whereas values exceeding the gross beta radioactivity detection limit of 30 mBq/L were found. The radioelement solubility in the studied systems varied according to the sequence radon > radium > other radionuclides and the higher porosity of sandstones relatively to basalts and diabases could justify the enhanced presence of dissolved radon in the porous aquifer. The implications of the data obtained in terms of standards established for defining the drinking water quality have also been discussed. The population-weighted average activity concentration for these radionuclides was compared to the guideline value of 0.1 mSv/yr for the total effective dose and discussed in terms of the choice of the dose conversion factors. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Natural radionuclides; Parana basin; Groundwater; Radiation dose